PROJECT MANAGEMENT IMPROVEMENT IN RUBY - Pahlevi Sofyan, Fikri
Project has been managed since the beginning of civilization, but nowadays projects are getting larger, riskier, and more complex, yet little progress on innovation and productivity has been made over the past 50 years (Sathanam, et al., 2020). Project underperformance, in terms of budget overrun and delayed completion is still one of many challenges in construction industry (KPMG, 2015). This research is to study about project failure which taking the case of Borneo II, project delivered by Ruby engineering and construction business line. Through available data source and conducted interview, it was found that some of the weak point of the project is in project controlling and lacking awareness about the project environment and project knowledge. Related to the weak point of project management process, recommendation has been given which is to refine the SOP, acquisition of project controlling software, improving knowledge management by conducting project management review as a media for peer assist, build up Community of Practice, building project dashboard and engineering & construction platform which connected and integrated with data analysis, data visualization and knowledge sharing platform, also to upgrade the people capabilities.